2022
DOI: 10.1002/maco.202213476
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the saliva formulation on brass corrosion

Abstract: The composition of natural saliva is strongly variable and unstable outside the oral cavity, therefore corrosion tests are usually performed in artificial saliva solutions. In this study the effect of the composition of various saliva solutions on the corrosion behavior of a CuZn37 alloy, exposed for 1, 3, and 16 h to the solutions, is investigated by using electrochemical measurements, optical microscopy, and X-ray photoelectron spectroscopy (XPS). The solutions investigated in this study are: Darvell, Carter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 17 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…In a recent work of the authors, 6 the corrosion behaviour of CuZn37 exposed to D, C‐B and SALMO formulations was investigated by electrochemical measurements, and it was found that the corrosion rate varied in the order: D > C‐B > SALMO. In this work, the corrosion behaviour can be correlated to the surface composition of the film formed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent work of the authors, 6 the corrosion behaviour of CuZn37 exposed to D, C‐B and SALMO formulations was investigated by electrochemical measurements, and it was found that the corrosion rate varied in the order: D > C‐B > SALMO. In this work, the corrosion behaviour can be correlated to the surface composition of the film formed.…”
Section: Discussionmentioning
confidence: 99%
“…In previous papers, the authors reported that, on brass alloy surfaces following the exposure of the samples to the model saliva solution, a thick surface film composed to a large extent of CuSCN and Zn 3 (PO 4 ) 2 was observed 4,5 . In a recent work, 6 the corrosion behaviour of CuZn37 exposed to Darvell (D), 7 Carter‐Brugirard (C‐B) 8 and SALMO 9 formulations was investigated by electrochemical measurements, and it was found that the corrosion rate determined after 16 h varies in the order: D (3.0 (0.3) μm/year) > C‐B (0.9 (0.2) μm/year) > SALMO (0.8 (0.2) μm/year). These three model saliva solutions were chosen from those of the literature due to their composition: All of them contain chlorides, thiocyanates, phosphates and carbonates, but they differ for the content in the organic compounds: D solution contains urea, lactic acid, trisodium citrate and uric acid; SALMO solution contains urea and glycine; C‐B solution contains only urea.…”
Section: Introductionmentioning
confidence: 97%
“…Citrate ions favored zinc dissolution, limiting the precipitation of the protective zinc phosphate layer. 11,12 In this paper, the effect of three artificial saliva formulations differing in the content of organic compounds on the corrosion resistance of the Ni-free DIN 1.4456 stainless steel is investigated. In fact, due to the widespread occurrence of nickel allergy, the European Commission prohibited the use of products with a Ni release higher than 0.5 μg/cm 2 per week.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It was demonstrated that when citrate was present, the thickness of the passive layer decreased, and the chromium and molybdenum oxide content in the passive film was higher than in the purely inorganic Hanks’ solution . In the framework of a project devoted to investigate the corrosion of brass wind instruments, the corrosion behavior of brass in different solutions simulating artificial saliva was studied, and it was shown that the presence of organic ligands in the formulation affects the corrosion rate, thickness, and composition of the surface film formed upon exposure of the brass to the solutions. Citrate ions favored zinc dissolution, limiting the precipitation of the protective zinc phosphate layer. , In this paper, the effect of three artificial saliva formulations differing in the content of organic compounds on the corrosion resistance of the Ni-free DIN 1.4456 stainless steel is investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation